Evaluation of the Application of Sales Tax Incentives on Luxury Goods to Motor Vehicle Sales During the Covid-19 Pandemic At Pt Hasjrat Abadi Manado Tendean Branch - William R. UMBOH; Harijanto SABIJONO; I Gede SUWETJA (PT Keberlanjutan Strategis Indonesia, 2023)
The Sales Tax on Luxury Goods incentive is a policy implemented by the Government which is a stimulus for the community's economy to increase and help restore the country's economy. This study aims to determine whether applying Sales Tax incentives on Luxury Goods on Motor Vehicles during the COVID-19 Pandemic affects Motor Vehicle Sales at PT Hasjrat Abadi Manado Tendean Branch. This research is descriptive qualitative research with the data used as primary data obtained from sources or informants. The results showed that the Sales Tax Incentive on Luxury Goods affects Motor Vehicle Sales at PT Hasjrat Abadi Manado Tendean Branch. This can be seen in the percentage increase in Motor Vehicle Sales of 112% for the first, 30% for the second, and 49% for the third period. Based on the data and discussion, a conclusion can be obtained that applying Sales Tax incentives on Luxury Goods during the COVID-19 period at PT Hasjrat Abadi Manado Tendean Branch is by applicable regulations and provisions.